Factors influencing access to higher education in La Rinconada, Peru: an ethnographic case study - Busch, AnneLiese M., author; Jennings, Louise, advisor; Lynham, Sue, committee member; Kuk, Linda, committee member; Sagas, Ernesto, committee member (Colorado State University. Libraries, 2020)
Studies show that there is a large gap in participation in higher education between Peru's poorest members of society and their wealthier counterparts despite the existence of 51 public universities located across Peru that are free of cost. Quantitative studies addressing this topic rely on a culture of poverty paradigm and have argued that this discrepancy is due to a lack of culture that prioritizes higher education among Peru's poor. The purpose of this study was to investigate why it is that the poorest segments of the population in Peru overwhelmingly do not pursue higher education despite the existence of tuition-free public universities, to understand the extent to which culture and systemic factors outside their control explain this phenomenon, and to examine how mining families perceive the role of and access to higher education for their children. This study focused on the community of La Rinconada, Peru for three primary reasons: (a) La Rinconada is representative of many illegal mining communities in not just Peru, but Latin America in that it is perceived as a city where low-skilled workers have an opportunity to generate more income working in the mines than by relying on positions that pay minimum wage (now 930 soles per month, which is equivalent to approximately $284); (b) more than 98% of La Rinconada's population is comprised of individuals belonging to the lowest socioeconomic level of Peruvian society; and (c) the population of La Rinconada has nearly quadrupled within the past decade and continues to grow. This study employed an ethnographic case study approach including recording and documenting observations of La Rinconada and Juliaca, the two sites in which the interviews were conducted, and conducting interviews with three separate groups of study participants including 14 teachers, 17 parents employed in a mining-related industry and 10 students. Field notes of all observations were kept and recorded as well as all interviews and conversations with the interview participants following their consent. The interviews were transcribed in Spanish and were then translated into English. Codes and patterns for each of the three groups of interview participants (teachers, parents employed in a mining-related industry, and students) were identified and were used to identify the three resulting themes. The observations I recorded and documented in La Rinconada demonstrate the harsh conditions of day-to-day life for its residents and highlight the extent to which the parents I interviewed are willing to go in order to provide a better life for their children; a life which for most participants included the pursuit of higher education. In the interviews I conducted I identified three themes: acceptance of harsh conditions for more opportunity, importance of higher education and the obstacles to pursuing it and the perceived role of higher education in future success. My findings indicate that for the parents employed in mining-related industries higher education was a priority because of the perceived financial and personal stability it would enable their children to enjoy and the social status and prestige a bachelor's degree would signify for their children because they would now be considered professional as opposed to a laborer. In general, for residents of La Rinconada, financial constraints and distance from institutions of higher education were identified as being the biggest obstacles to accessing higher education. My findings show that despite the fact that half of the individuals I interviewed had not pursued higher education themselves, all of the participants stated that they valued higher education and viewed it as essential to achieving financial and personal stability and they emphasized their desire for their children to pursue higher education.
Keywords: economic; ethnographic; poverty; education; access; Peru